DESIGN OF PERSONNEL PERFORMANCE SYSTEM USING MANAGEMENT BY OBJECTIVES (MBO) METHOD - Rustam Effendi; Andi Usri Usman (LPPM Unbaja, 2019)
In the current era of globalization, government agencies in general operate their management using a computerized system. The system is a collection of elements / elements that are interrelated and influence each other in carrying out joint activities to achieve a goal. The system is very necessary in an organization or company, or service. The smooth running of government and development is very dependent on the performance of the state apparatus, especially the Civil Servants as development planners and implementers. In completing various tasks and responsibilities that constitute an effort to carry out the duties of the Civil Servant, the employee needs to be fostered as well as possible. Performance appraisal is known by the term performance rating, performance appraisal, personnel assessment, employee evaluation is an evaluation activity carried out by the Office or company on employee work performance. Employees are people who are employed in a particular body, both in government institutions and in business entities. An employee appraisal method, namely management by objectives, is a process of approval of objectives within an organization so that management and employees approve these objectives and understand what their position is in the organization.